2009
DOI: 10.1161/circulationaha.108.783688
|View full text |Cite
|
Sign up to set email alerts
|

Get With the Guidelines–Stroke Is Associated With Sustained Improvement in Care for Patients Hospitalized With Acute Stroke or Transient Ischemic Attack

Abstract: Background-Adherence to evidence-based guidelines for treatment of stroke or transient ischemic attack is suboptimal.We sought to establish whether participation in Get With the Guidelines-Stroke was associated with improvements in adherence. Methods and Results-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
538
2
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 513 publications
(559 citation statements)
references
References 29 publications
12
538
2
7
Order By: Relevance
“…Although several studies have reported on means of improving the timeliness of thrombolysis in acute stroke, [14][15][16][17][18]25 none has specifically focused on public safety net hospitals, which generally have less funding and treat more underor uninsured patients. As one of these hospitals, our institution treats a diverse and relatively socioeconomically disadvantaged population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have reported on means of improving the timeliness of thrombolysis in acute stroke, [14][15][16][17][18]25 none has specifically focused on public safety net hospitals, which generally have less funding and treat more underor uninsured patients. As one of these hospitals, our institution treats a diverse and relatively socioeconomically disadvantaged population.…”
Section: Discussionmentioning
confidence: 99%
“…16 Other quality improvement initiatives, including the national "Get With The Guidelines-Stroke" initiative, have demonstrated similar success. 17,18 Interventions aimed at reducing time-to-thrombolysis are less well studied and may be more difficult to implement in public safety net hospitals. Such institutions face unique challenges related to reduced funding levels and care provision for larger proportions of socioeconomically disadvantaged patients, underinsured patients, and ethnic minorities.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the design and conduct of the program have been previously described. 12 GWTG uses a web-based patient management tool (Outcome, Quintiles Company) to collect clinical data on consecutively admitted patients, to provide decision support, and to enable real-time online reporting features. After an initial pilot phase, the GWTG-Stroke Program was made available in April 2003 to any hospital in the United States.…”
Section: Methodsmentioning
confidence: 99%
“…Although the GWTG-Stroke program is overrepresented with larger academic teaching hospitals, the patient demographics and comorbidites are similar to those described in other stroke registries and administrative databases. 12 Outcome Sciences serves as the data collection and coordination center for GWTG. The Duke Clinical Research Institute serves as the data analysis center and has an agreement to analyze the aggregate deidentified data for research purposes.…”
Section: Methodsmentioning
confidence: 99%
“…The American Heart Association (AHA) and American Stroke Association GWTG‐Stroke database data collection methods have been described previously 7, 8, 9, 10. In brief, participating hospitals used the AHA's Internet‐based Patient Management Tool (Quintiles) to enter data, receive decision support, and obtain feedback via on demand reports of performance on quality measures and recorded data from consecutive admissions for acute ischemic stroke.…”
Section: Methodsmentioning
confidence: 99%